Effect of different substrates on functional performance and kinase activation during reperfusion after ischaemia in hearts from obese insulin resistant rats - Fan, WenJun (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017